Investigating Civil Engineering Students' Vocabulary Learning Strategies at Ambon State Polytechnic - Grace Hansina Labetubun; Rosina Fransisca Joan Lekawael; Marcy Saartje Ferdinandus (Journal of Language Education and Educational Technology (JLEET), 2022)
This research aims to investigate the use of vocabulary learning strategies used by D3 civil engineering students. This study was descriptive quantitative design and employed survey design. Vocabulary Learning Strategies (VLSs) questionnaire adopted from Puangsang (2018) was the main instrument in collecting the quantitative data. The data analysis shows determination strategies (M=3.32) is the most used strategies and followed by metacognitive strategies (M=3.05), memory strategies (M=2.87), social strategies discovery (M=2.78), cognitive strategies (M=2.56), and social strategies consolidation (M=1.82)